Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Genotoxic and oxidative stress assessment of heavy metal contaminated soil and water in human blood and bovine milk samples from the different industrial zones of Punjab, Pakistan - Muhammad Muddassir Ali; Furqan Awan; Muhammad Usman Jamil; Muhammad Ijaz; Asad Ullah; Wasim Shehzad (Journal of Trace Elements in Medicine and Biology, 2025)

Erratum to “Improved project control for sustainable development of construction sector to reduce environment risks” [J. Clean. Product. (2019) 118214] - Summaira Malik; Fareena Fatima; Asma Imran; Lai Fatt Chuah; Jirí Jaromír Klemes; Imran Hameed Khaliq; Saira Asif; Muhammad Aslam; Farrukh Jamil; Abdullah Khan Durrani; Majid Majeed Akbar; Muhammad Shahbaz; et al. (Journal of Cleaner Production, 2024)

Resilient mechanism of strigolactone (GR24) in regulating morphological and biochemical status of maize under salt stress - Iqra Iftikhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Shamsa Rana; Fozia Farhat; Hira Farooq; Kamran Ahmad; Muhammad Jamil; Fasih Ullah Haider; Saltanat Aghayeva (Biocatalysis and Agricultural Biotechnology, 2024)

Do green entrepreneurial orientation and green knowledge management matter in the pursuit of ambidextrous green innovation: A moderated mediation model - Muhammad Usman Shehzad; Jianhua Zhang; Khawaja Fawad Latif; Khalid Jamil; Abdul Hakeem Waseel (Journal of Cleaner Production, 2023)

Facies Analysis and Sedimentary Architecture of Hybrid Event Beds in Submarine Lobes: Insights from the Crocker Fan, NW Borneo, Malaysia - Muhammad Jamil; Numair Ahmed Siddiqui; Nisar Ahmed; Muhammad Usman; Muhammad Umar; Hamad ur Rahim; Qazi Sohail Imran (Journal of Marine Science and Engineering, 2021)
Hybrid event beds represent the combined effect of multiple geological processes, which result in complex depositional geometries and distinct facies distribution in marine environments. Previous work on hybrid event beds highlights the classification, origin, and types of hybrid facies. However, in the present study, we discuss the development of hybrid event beds in submarine lobes with an emphasis on the analysis of proximal to distal, frontal to lateral relationships and evolution during lobe progradation. Detailed geological fieldwork was carried out in the classical deep-marine Late Paleogene Crocker Fan to understand the relationship between the character of hybrid bed facies and lobe architecture. The results indicate that hybrid facies of massive or structureless sandstone with mud clasts, clean to muddy sand, and chaotic muddy sand with oversized sand patch alternations (H1–H3) are well developed in proximal to medial lobes, while distal lobes mainly contain parallel to cross-laminated clean to muddy hybrid facies (H3–H5). Furthermore, lateral lobes have less vertical thickness of hybrid beds than frontal lobes. The development of hybrid beds takes place in the lower part of the thickening upward sequence of lobe progradation, while lobe retrogradation contains hybrid facies intervals in the upper part of stratigraphy. Hence, the development of hybrid beds in submarine lobe systems has a significant impact on the characterization of heterogeneities in deep-marine petroleum reservoirs at sub-seismic levels.